Formulasi Benada Smoothies Dari Bengkuang, Buah Naga Merah, dan Dadih sebagai Camilan Berserat, Antioksidan, Probiotik Untuk Diabetes Melitus - Marni Handayani; Suparman Suparman; Nur Fauziah; Mulus Gumilar (Poltekkes Kemenkes Padang, 2025)
The prevalence of diabetes mellitus in Indonesia increased from 10.9% in 2018 to 11.7% in 2023, based on the Indonesian Health Survey. Individuals with type 2 diabetes are advised to consume low glycemic index, high-fiber, and nutritionally balanced foods, including snacks that help regulate blood glucose levels. This study aimed to develop smoothie formulations made from jicama, red dragon fruit, and dadih (fermented buffalo milk) as a functional snack for diabetic patients. A laboratory-scale experimental design was applied using three formulations: F1 (50:50:30), F2 (60:40:30), and F3 (70:30:30). Organoleptic testing was conducted using a 7-point hedonic scale with 25 panelists. Nutritional evaluations included proximate analysis, fiber (acid-base hydrolysis), antioxidant activity (DPPH method), and probiotic content (reference-based). Organoleptic data were analyzed using the Kruskal-Wallis test (p<0.05). A significant difference was found in color (p=0.001), but not in aroma, taste, texture, or overall preference. The best formulation, F1, received the highest overall score (5.36). Per 100 g, the product contained 57.71 kcal, 1.71 g protein, 1.15 g fat, 10.13 g carbohydrates, 1.06 g fiber, IC₅₀ antioxidant value of 23,496.69 ppm, and probiotic count of 8.81×10⁵ CFU/g. The conclusion is Benada smoothies, particularly F1, were well accepted and show potential as a snack for diabetes. Further research is recommended to evaluate its effect on blood glucose and optimize antioxidant content.